Catalytic upgrading of biomass-derived pyrolysis vapour over metal-modified HZSM-5 into BTX: a comprehensive review - Balasundram, Vekes; Norazana, Ibrahim; Rafiziana, Md. Kasmani; Ruzinah, Isha; Mohd. Kamaruddin, Abd. Hamid; Hasrinah, Hasbullah (Springer, 2020)
This paper provides an updated and comprehensive review on the catalytic upgrading of biomass-derived pyrolysis vapours over metal-modified HZSM-5 catalyst into bio-aromatic hydrocarbons. The catalytic upgrading of biomass pyrolysis vapours seems to be a promising technology in generating gasoline-type bio-aromatic hydrocarbons, i.e. benzene, toluene and xylene (BTX). Biomass-derived raw pyrolysis oil has high oxygenated compounds that deteriorate pyrolysis oil properties and limits its applications. Metal modification of hydrogen exchanged Zeolite Socony Mobil Five (HZSM-5) catalyst has gained attention in a biomass pyrolysis research area due to the beneficial effects on upgrading the oxygenated pyrolysis vapours into BTX-enriched pyrolysis oils. The influence of metals (alkali and alkaline earth metals, transition metals and rare earth metals) as bi-functional or multifunctional activity on HZSM-5 catalyst during pyrolysis has been addressed. The effect of reaction temperature, the type of metals, metal contents, the silica-to-alumina ratio of catalyst and the catalyst-tobiomass ratio are critically discussed for maximum production of monocyclic aromatic hydrocarbons during the upgrading of pyrolysis vapours. Finally, concluding remarks on metal-modified zeolite catalyst and future recommendation in upgrading biomass pyrolysis vapours are presented.